Bibliometric analysis of school improvement research: A century of scholarly contributions - Arjanto, Paul; Bafadal, Ibrahim; Atmoko, Adi; Sunandar, Asep (Jurnal Akuntabilitas Manajemen Pendidikan, 2023)
This study aims to comprehensively review the historical development and current status of research in the field of school improvement using a bibliometric analysis approach. Recognizing the vital role of schools in society and the necessity for their constant evolution, it is essential to understand the breadth and depth of scholarly efforts in school improvement. Using the Scopus index, 596 English language journal articles on school improvement published between 1916 and 2023 were identified and analyzed. Utilizing the VOSviewer software, the bibliometric analysis was conducted in two stages: descriptive statistics to understand the trend of document volumes and co-authorship countries, and a multidimensional scaling technique to visualize co-authorship, co-occurrence, and citation networks. The data revealed a consistent rise in publication volume over the years, with a peak in 2020. Despite contributions from 45 countries, the United States and the United Kingdom were the most prolific. However, author collaboration was found to be minimal, suggesting potential for broader partnerships. The study also identified key research themes such as leadership, distributed leadership, and accountability through keyword co-occurrence analysis. The most frequently cited literature emphasized the role of collaboration, instructional program coherence, and school culture in school improvement. The findings underscore the necessity for increased global collaboration, exploration of emerging themes, and enhanced geographical representation in future research to further enrich the knowledge base in this vital educational field.